Fragmentation of the Global Monetary and Financial System in the Context of Rising Geopolitical Tensions - Aleksei V. Kuznetsov (Vestnik RUDN. International Relations)
The global monetary and financial system, as a form of organization of international monetary and financial relations, is designed to provide framework conditions for the unimpeded exchange of goods, services and capital between countries, in order to maintain sustainable economic growth. Currently, the functionality of the international currency standard is exposed to the influence of disintegration processes in the global economy and global finance, which are caused by the growth of geopolitical tensions. The purpose of the article is to identify and characterize the main institutional aspects of the fragmentation of the global monetary and financial system, taking into account their impact on the transformation of the global financial architecture. It is demonstrated that the geopolitical rivalry between the United States and China is caused by the desire to overcome their interdependence in the areas of global supply chains and the production of new-generation semiconductors, respectively. The article discusses the main trends that are currently characterizing the fragmentation of the global monetary and financial system, such as institutional dysfunctionality, the bloc confrontation between mature and emerging financial and economic centers, de-dollarization of international reserves and digitalization of international settlements. The article substantiates the influence of these trends on the transformation of the global financial architecture, which is manifested in the crisis of the institutional foundations of the global monetary and financial system and the chaotic reorganization of international monetary and financial relations under the influence of digitalization processes. The article identifies the reasons for the institutional dysfunctionality of the global monetary and financial system, including the decline in the role of the International Monetary Fund (IMF) as a lender of last resort and the loss of state control over the growth of the money supply in the global economy. It also examines the factors explaining the motivation of central banks to diversify the structure of official foreign exchange reserves. Particular attention is paid to the problem of introducing central bank digital currencies as a method of counteracting the asymmetric use of the US dollar at the international level and as a way of improving international financial stability. It is concluded that changing the position of the US dollar in the global financial architecture, as a key international liquidity, depends on the efforts of the world’s majority countries in creating a systemic alternative to the current international monetary order based on advanced financial technologies.